Retrospective cohort study of health service use for cardiovascular disease among adults with and without a record of injury hospital admission. Issue 11 (3rd November 2020) - Randall, Sean M; Wood, Fiona M; Fear, Mark W; Boyd, James; Rea, Suzanne; Duke, Janine M
Abstract : Objective: To quantify postinjury cardiovascular-related health service use experienced by mid to older aged adults hospitalised for injury, compared with uninjured adults. Additionally, to explore the effect of beta-blocker medications on postinjury cardiovascular hospitalisations among injury patients, given the potential cardioprotective effects of beta blockers. Design: A retrospective cohort study using linked administrative and survey data. Participants: Records of 35 026 injured and 60 823 uninjured matched adults aged over 45 from New South Wales, Australia, who completed the 45 and up survey. Primary and secondary outcome measures: Admission rates and cumulative lengths of stay for cardiovascular hospitalisations, and prescription rates for cardiovascular medications. Negative binomial and Cox proportional hazards regression modelling were used to generate incident rate ratios (IRRs) and HR. Results: Compared with the uninjured, those with injury had a 19% higher adjusted rate of postinjury cardiovascular admissions (IRR 1.19, 95% CI 1.14 to 1.25), spent 40% longer in hospital for ardiovascular disease (IRR 1.40, 95% CI 1.26 to 1.57) and had slightly higher cardiovascular prescription rates (IRR 1.04, 95% CI 1.02 to 1.06), during study follow-up. Those in the injury cohort that used beta blockers both prior to and after injury (continuous) appeared to have reduced need for post-injury cardiovascular hospitalisation (IRR 1.09, 95% CI 1.17 to 1.42) compared with those commencing on beta blockers after injury (after 30 days: IRR 1.69, 95% CI 1.37 to 2.08). Conclusions: Apparent increased postinjury hospitalisation rates and prolonged length of stay related to cardiovascular disease suggest that injury patients may require clinical support for an extended period after injury. Additionally, injury patients who were on continuous beta blocker treatment appeared to have lower need for post-injury cardiovascular hospitalisations. However, the data do not allow us to draw clear conclusions and further clinical research is required.